Komik Digital "Di Balik Topeng" Media Informasi Kewaspadaan Obat Ilegal dan tidak aman - Laila Puspitasari, Sarah; Hidayat, Syarip; Kadarisman, Asep (Visualita Jurnal Online Desain Komunikasi Visual, 2025)
Health issues have become a major public concern, driving significant developments in the health sector. However, this situation is exploited by certain individuals selling unsafe and illegal drugs that pose serious health risks. Weak supervision by BPOM and low public awareness about medications worsen the circulation of such drugs. Therefore, an informative medium is needed to raise public awareness about drug consumption. This qualitative research was conducted through literature studies, observations, interviews, and questionnaires. Data were analyzed through reduction, presentation, and verification stages. The findings show that most respondents lack understanding of illegal drugs and tend to buy medicines without checking their safety. Respondents also showed strong interest in educational media that are visual and engaging, such as digital comics. The design process applies visual communication design and storytelling approaches, combining narrative strength with communicative visuals. The stages include idea exploration, script writing, character and background visualization, and digital comic page production. Digital comics are chosen for their ability to effectively, attractively, and deliver health messages, raising awareness and caution about the dangers of illegal drugs.